Schisandrin B Inhibits Osteoclastogenesis and Protects Against Ovariectomy-Induced Bone Loss - Wang, Jia; Fang, Zhong; Song, Chao; Kang, Honglei; Guo, Qian; Dong, Yimin; Zhang, Ya; Peng, Renpeng; Guan, Hanfeng; Li, Feng (Frontiers in Pharmacology, 2020)
Osteoporosis is a systemic skeletal disease which is highly prevalent worldwide and considered to be associated with excessive bone resorption mediated by osteoclast. Osteoclast differentiation is characterized by the activation of inflammation-related pathways and the generation of reactive oxygen species (ROS). Schisandrin B is a bioactive compound with strong anti-inflammation and anti-oxidative properties, we thus speculated that Schisandrin B might serve as a potential candidate for osteoporosis. In the present study, we found that the formation and function of osteoclasts were dramatically suppressed by Schisandrin B. And consistent with the in vitro results, treatment with Schisandrin B attenuated ovariectomy-induced bone loss in mice. Moreover, Schisandrin B notably inhibited the activation of mitogen activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) pathways and scavenged ROS by activating nuclear factor E2 p45-related factor 2 (Nrf2) signaling. In conclusion, our study indicates that Schisandrin B is an effective approach to treat osteoporosis and other osteoclast-related diseases.